PENGGUNAAN BAHASA ISYARAT PADA TAYANGAN BERITA INEWS TV DALAM RANGKA MEMAHAMI INFORMASI PENYANDANG TUNARUNGU - Andre Kurniawan (2019)
The dissemination of information via television media has proved that it has not been completely effective or fully felt by all Indonesians, especially for the communities of deaf disabilities. According to data from the Ministry of the Social Republic of Indonesia through the information system for people with disability, there are 209,604 people. Based online-based observation on the writer's field, the news focused iNews TV material connecting point for hearing disabilities as well as the best news channel in Indonesia, with so many awards received by iNeThishis is why iNews also selects highly professional sign language experts in his field. The study aims to provide input and provide material for television stations about the use of sign-language translation in news programs to meet the need information on the people and also to increase knowledge for nonverbal interpretation and for those with deaf disabilities. The theory used in this research is nonverbal communication. The data-collection technique used in this study is interviews, observation, and documentation. The findings of this research iNews TV are enough to meet the needs of informants by providing fresh information and easy-to-understand visuals. Jbi iNews TV that meets adequate qualifications for delivery